Repercussions of marital infidelity in Malaysia: a legal response - Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Abdul Hak, Nora; Md Said, Muhamad Helmi (2018)
Marital infidelity has become one of the most traumatic life experiences in the society today. It is the greatest danger threatening family life and destroys marriages thus leading to increased divorce rates in the society. This is because it signals relationship problems between couples. There are diverse causes of widespread marital infidelity, which is common in our society today. The causes include marriage boredom, unrealistic expectations, conflicts and misunderstandings of one another. As in many jurisdictions, marital infidelity is not an offence under the law in Malaysia but there are some legal remedies or avenues that can be sought to curtail the re- occurrence of such problem. The objectives of the paper are to discuss the legal repercussion of marital infidelity in Malaysia and whether solution through enforcement of law is an adequate mechanism to curb this social problem. The methodology adopted in this paper is based on the content analysis of reports, case laws, leading textbooks and journal articles. The paper is significant as it addresses crucial concerns raised in reference to the current laws relating to the protection of the marriage and family institutions in Malaysia. It concludes with a series of recommendations and suggestions for improvement in finding an appropriate legal mechanism in curbing the issue of marital infidelity for the preservation of family institution as a whole.